Vijjādharanaya ññvanʻʹ poṅʻʺ kyamʻʺ (Tuiṅʻʺ raṅʻʺ Cheʺ paññā Ūʺ cīʺ Ṭhāna, 1993)
Processing of metallic and non-metallic salts for use in preparing Burmese indigenous medicine; textbook for prescribed course of study.